The effect of maternal low flow oxygen administration during the second stage of labour on umbilical cord artery pH: a randomised controlled trial. (March 2017) - Qian, G; Xu, X; Chen, L; Xia, S; Wang, A; Chuai, Y; Jiang, W
Abstract : Objective: To assess the effect of maternal low flow oxygen administration during the second stage of labour on umbilical cord artery pH. Design: A randomised controlled trial. Setting: A tertiary teaching hospital in China. Population: Women in the second stage of labour with no complications. Methods: About 443 women were randomly allocated to receive either supplemental oxygen at a flow rate of 2 l/min or a sham supplementation by nasal cannula. Healthcare providers, women and outcome assessors were blinded to allocation. Main outcome measures: Umbilical cord artery pH and fetal heart rate (FHR) pattern. Results: Baseline characteristics were similar between the two groups. There were no significant differences between the two groups in the umbilical cord artery pH [median 7.261, interquartile range (IQR) 7.228–7.295 versus 7.266 (IQR 7.232–7.297), P  = 0.64], the proportion with pH less than 7.2 [30/219 versus 34/224, P  = 0.66, RR (relative risk) 0.9, 95% CI 0.57–1.42], and the proportion with normal FHR pattern (147/219 versus 153/224, P  = 0.79, RR 0.98, 95% CI 0.86–1.12). Maternal partial pressure of dissolved oxygen was significantly higher in the oxygen group than in the sham group [median 150.0 mmHg (IQR 142.6–156.7) versus 112.0 (IQR 104.8–118.3), P  < 0.001], whereas carbon dioxide was significantly lower in the oxygen group than in the sham group (mean difference −1.1, 95% CI −2.1 to −0.1, P  = 0.03). Conclusion: The use of 2 l/min maternal oxygen during the second stage of labour did not adversely affect either the umbilical artery pH or the FHR pattern distribution. Tweetable abstract: No difference in abnormal fetal acid base or normal heart rate if maternal O2 given, randomised trial finds. Tweetable abstract: No difference in abnormal fetal acid base or normal heart rate if maternal O2 given, randomised trial finds.